The role of hypoxia-inducible factor-1 alpha in multidrug-resistant breast cancer - Yong, Liyun; Tang, Shasha; Yu, Haixin; Zhang, Hongyi; Zhang, Yi; Wan, Yuan; Cai, Fengfeng (Frontiers in Oncology, 2022)
Breast cancer is the most common cancer in women worldwide with increasing incidence. Significant therapeutics advances in the field of breast cancer have resulted in a growing number of treatment options, whereas de novo or acquired resistance is still a persistent clinical challenge. Drug resistance involves a variety of mechanisms, and hypoxia is one of the many causes. Hypoxia-inducible Factor-1 Alpha (HIF-1α) is a key transcription factor which can regulate the response of cells to hypoxia. HIF-1α can trigger anaerobic glycolysis of tumor cells, induce angiogenesis, promote the proliferation, invasion, and migration of tumor cells, and lead to multidrug resistance. This review mainly discussed the role of HIF-1α in the drug-resistant breast cancer and highlighted the potential of HIF-1α -targeted therapy.